QURUQLIK QORINOYOQLI MOLLYUSKALARI RADULASINING TUZILISHI VA TIPLARI - Ochilova , Charos (Actual problems and prospects of the study of the fauna, 2024)
The radula has been widely used as a structural study object in the study of the gastropoda class. Research is growing rapidly on the anatomy and morphology of the scientific radula, but also on the relationship between the radula and food type, or the radula and interrelationships. In naming new species, the radula also played a role in revising species in the genus. Differences in the shape and structure of the radula are strongly influenced by the type of mollusk. The radula is such an important part of the life of many molluscs that it is often overlooked.